NILAI RELIGIUS PADA CERPEN LELAKI DARI TANJUNG NIPAH KARYA E.WIDIANTORO - NFN Musfeptial (tuahtalino, 2017)
Men from Tanjung Nipah short story is a short story by E. Widoantoro rich in religious values. Thus, the study of religious values in this short story interesting to do. This research tries to explain religious value in literature. In addition, this study also was supported by descriptive analysis method. The results showed the existence of religious values on the short story of the man Tanjung Nipah. Value religus visible of the three protagonists in this short story, the characters Ustad Abu, Wak Hassan and Prime. As a faith mosque, Ustad Abu figure is a religious figure, both in daily activities and in religious activities. In daily life, figures Ustad Abu maintain close ties with all the citizens of Tanjung Nipah. So is the case with Hasan Wak figures, exemplary shown, make him a role model for the community Tanjung Nipah. It is also shown by the figures diperlhatkan prime, he is a devout young child so he also became a fad for young people in Tanjung Nipah.